2003
DOI: 10.1016/s0883-2927(03)00078-7
|View full text |Cite
|
Sign up to set email alerts
|

The solid state partitioning of contaminant metals and As in river channel sediments of the mining affected Tisa drainage basin, northwestern Romania and eastern Hungary

Abstract: The solid state partitioning of metals and As in river channel sediments has been investigated along an 828 km study reach comprising the rivers Lapuş, Someş and Tisa, using a 4-stage sequential extraction procedure (SEP) that identified 4 chemical phases: (1) exchangeable, (2) Fe and Mn oxides, (3) organic matter/sulphides and (4) residual. Peak total concentrations of As (240 mg kg−1), Cd (95 mg kg−1), Cu (24,500 mg kg−1) and Pb (21,100 mg kg−1) were found in the River Lapuş immediately downstream of Băiuţ b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 42 publications
7
60
1
5
Order By: Relevance
“…Compared to our results with earlier studies about elemental concentration in different river surface sediment, our study indicated the moderate level of pollution in the Upper Tisza region. Bird et al (2003) ) was higher in the surface sediment than our findings (Bird et al 2003). Vystavna et al (2012) ), and in the case of Velke Kozmalovce, the Pb concentration was lower 66±8 mg kg −1 compared to our results.…”
Section: Discussioncontrasting
confidence: 83%
“…Compared to our results with earlier studies about elemental concentration in different river surface sediment, our study indicated the moderate level of pollution in the Upper Tisza region. Bird et al (2003) ) was higher in the surface sediment than our findings (Bird et al 2003). Vystavna et al (2012) ), and in the case of Velke Kozmalovce, the Pb concentration was lower 66±8 mg kg −1 compared to our results.…”
Section: Discussioncontrasting
confidence: 83%
“…But earlier report of pollution control Board reveals that they have discharge the effluents of high concentration of Chromium to the river Salandi [18]. Although, at present, some chromite mines are not running, but the mining effluents left by them earlier without proper treatment has resulted open exposure of chromite mixed soil to the atmosphere and pollute the river Salandi with chromium through atmospheric rain precipitations as river Salandi is the only natural drainage system in the study area [5,9,30,47,54,68,69]. Hence more concentration of Cr 6+ is found from Bidyadharpur to Baudpur in the month of August and October is due to entry of mining discharges, industrial discharges [17], agricultural effluents, atmospheric rain precipitation and geology of river bed and catchment area [29,67].…”
Section: +mentioning
confidence: 98%
“…Major attention was given to the mining impact on the quality of water, and the content in heavy metals (cadmium, lead, copper, manganese, zinc, iron, arsenic etc) using various investigation techniques (Bird, et al, 2003;Macklin, et al, 2006;Kraft, et al, 2006;Roman, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%